2012
DOI: 10.1177/1403494812459600
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive health: Health in Sweden: The National Public Health Report 2012. Chapter 9

Abstract: In many ways our sexual and reproductive health reflects our way of life and living conditions. In a long-term perspective, advances in welfare combined with a well-developed health and medical care system, have meant that by international standards it is now rare for mothers to die during delivery and infant mortality continues to decline to new record lows. Pregnancy and childbirth, however, continue to be a time in a woman's life associated with many health problems, and absence from work due to illness is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 38 publications
4
36
0
1
Order By: Relevance
“…Danish data also showed that the risk for travel-associated gonorrhoea in men is six times higher compared with women. This is consistent with the finding that younger people and men are more likely to report having a new sex partner while travelling [16]; younger people are also more likely to have a higher number of sex partners in general [17], which is a risk factor for having a new sex partner while overseas [16]. …”
Section: Discussionsupporting
confidence: 88%
“…Danish data also showed that the risk for travel-associated gonorrhoea in men is six times higher compared with women. This is consistent with the finding that younger people and men are more likely to report having a new sex partner while travelling [16]; younger people are also more likely to have a higher number of sex partners in general [17], which is a risk factor for having a new sex partner while overseas [16]. …”
Section: Discussionsupporting
confidence: 88%
“…Since participation rate was only 14%, one may argue for a selection bias related to reproductive capacity but this seems somewhat unlikely, since pregnancy rates are as low as 3% in Swedish 15–19 year-old women [49] and only 19 (6.4%) out of the 295 included men reported to have made a partner pregnant and 11 men (3.7%) to have had regular unprotected intercourse during at least a year without causing a pregnancy. Further, similar semen parameters have been found in conscripts and men recruited through schools or through other participants [50].…”
Section: Discussionmentioning
confidence: 99%
“…Rates of gonorrhoea infection have risen in both countries over recent years 5 18. Previous research has found that almost half (43% in 2011) of Swedish men who are infected with gonorrhoea by women acquire the disease abroad, especially in Thailand 18. German backpackers were less likely than Britons to engage in unsafe sex due to lower levels of new partner acquisition.…”
Section: Discussionmentioning
confidence: 99%